A fat chance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Statistical methods for Agricultural Experiments: A reference manual for researchers in the Pacific islands states By D Hunter, IRETA, 2001. 41 pp. ISBN 982 175 148 2 US$ 20 Euro 22.30